Beta-cariofileno atenua dano cognitivo induzido pela exposição ao aspartame em ratos pela modulação da atividade da acetilcolinesterase e da Via BDNF/TrKB - Rosa, Érica Vanessa Furlan (2021)
Aspartame (ASP) is a widely used as a tabletop sweetener and sucrose substitute in many food matrices. However, several studies have reported that exposure to ASP can damage biological tissues, such as the central nervous system and causing behavioral changes, such as learning and memory deficits. In this sense, β-caryophyllene (BCP) is a natural pharmacologically active molecule that can be found in several foods such as bread, coffee, alcoholic beverages and spices. Of particular importance, both ASP and BCP are commonly consumed and may even be present at the same meal. Thus, the aim of this study was to evaluate the potential protective effect of BCP against cognitive damage induced by repeated exposure to ASP in rats as well as the putative involvement of the BDNF / TrkB signaling pathway and the activity of acetylcholinesterase (AChE). In addition, some plasma markers of liver and kidney function and lipid profile were also evaluated. The Ethical Research Committee of Federal University of Santa Maria approved all experimental procedures carried out in the present study. Male Wistar rats received ASP (75 mg/kg; i.g.) and/or BCP (100 mg/kg; i.p.) once daily for 14 days. At the end of the treatment protocol, the animals performed the behavioral tasks of open field and object recognition, and then samples of cerebral cortex, hippocampus and blood were collected for biochemical and molecular analyses. The results showed that ASP exposure impaired short- and long-term memory compared to the control group. Treatment with BCP was effective in protecting against cognitive damage. In addition, ASP exposure increased AChE activity, which was prevented by BCP administration. Molecular markers indicated increased levels of BDNF and TrkB in the hippocampus of rats treated with BCP, suggesting greater activation of this pathway. Regarding plasma parameters, ASP induced changes in ALT activity and HDL levels, while BCP was effective in reducing values to those of the control group. In conclusion, the study demonstrated that BCP protected against memory impairment induced by exposure to ASP, which may be associated with a modulation of AChE activity and the BDNF / TrkB signaling pathway.